A Surface‐Tailoring Method for Rapid Non‐Thermosensitive Cell‐Sheet Engineering via Functional Polymer Coatings. Issue 16 (11th March 2020) - Baek, Jieung; Cho, Younghak; Park, Hyun‐Ji; Choi, Goro; Lee, Jong Seung; Lee, Minseok; Yu, Seung Jung; Cho, Seung‐Woo; Lee, Eunjung; Im, Sung Gap
Abstract: Cell sheet engineering, a technique utilizing a monolayer cell sheet, has recently emerged as a promising technology for scaffold‐free tissue engineering. In contrast to conventional tissue‐engineering approaches, the cell sheet technology allows cell harvest as a continuous cell sheet with intact extracellular matrix proteins and cell–cell junction, which facilitates cell transplantation without any other artificial biomaterials. A facile, non‐thermoresponsive method is demonstrated for a rapid but highly reliable platform for cell‐sheet engineering. The developed method exploits the precise modulation of cell–substrate interactions by controlling the surface energy of the substrate via a series of functional polymer coatings to enable prompt cell sheet harvesting within 100 s. The engineered surface can trigger an intrinsic cellular response upon the depletion of divalent cations, leading to spontaneous cell sheet detachment under physiological conditions (pH 7.4 and 37 °C) in a non‐thermoresponsive manner. Additionally, the therapeutic potential of the cell sheet is successfully demonstrated by the transplantation of multilayered cell sheets into mouse models of diabetic wounds and ischemia. These findings highlight the ability of the developed surface for non‐thermoresponsive cell sheet engineering to serve as a robust platform for regenerative medicine and provide significant breakthroughs in cell sheet technology. Abstract : A novel, non‐thermoresponsive cell‐sheet engineering approach is developed by a surface energy‐controlled polymer coating combined with regulation of the surface‐energy‐controlled and transiently changing the divalent cation concentration. An efficient, gentle triggering method enables the release of an intact cell sheet within 100 s under physiological conditions (pH 7.4 and 37 °C), enhancing the therapeutic potential of the cell sheets.